(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Due to their chronic condition, immunologically mediated mucocutaneous illnesses represent a sizable group of oral mucosal disorders that negatively impact patients’ quality of life. Treatment for these conditions should aim to address the underlying immunological dysregulation, stop recurrences, and maintain organ integrity and function in addition to relieving symptoms. Immunosuppressants are mostly used to treat certain illnesses. Existing comorbidities, recurrent relapses or brief disease-free intervals, long-term pharmaceutical use, and its consequences provide challenges in the treatment of these disorders. This study focuses on more recent immunosuppressants and how they relate to conditions of the oral mucosa.